الرجوع عن الشهادة وأثره فى القضاء : رؤية فقهية معاصرة - سومائيلا، سافاني (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This research aims to study the law related to the retraction of testimony and its judiciary impacts, and the most important issues dispersed in various books of jurists, as discussed by classical jurists from the four well known schools and other schools of Islamic law. The study attempts to clarify the legality, definition, proofs, pillars, conditions and types of retraction of testimony. In addition, it explains the dissimilarity between the topic and retraction of self-confession, as well as its causes and domains. It also discusses various scholars' views on the liability of the witnesses when they disavow the testimony in three contexts: before the judgment; after it and before its execution; or after both judgment and its execution. The study also analyses the different views on the confirmation or nullification of the verdict following retraction of a witness from his/her testimony. The study used descriptive and analytical methods to examine diverse views and texts, while the disputed (controversial) issues of the topic were evaluated using the inductive method. The study concludes that judgment should not be based on testimony retracted before it, and the witnesses in that case should not be penalized for issues related to wealth; but should be punished with hadd punishment if it is related to zina because of their false accusation of zina; and be punished with discretionary punishment if it is related to other than zina and done intentionally. The study also finds that according to preferable view, if the witnesses retract from their testimony after the judgment and before its execution and it is related to wealth, the verdict should be executed and witnesses should be compelled to liability. If the retraction from the testimony occurs after the execution of the verdict and it is related to wealth, the witnesses should be charged with penalty; while if it is related to dam (blood) and it is done intentionally, they should be punished with just retribution (qisas). However, if they have witnessed mistakenly, they have to pay blood money (diyyah).